Cervical cancer cell–derived angiopoietins promote tumor progression - Ping Yang; Na Chen; Dongyun Yang; Janet Crane; Bangxing Huang; Ruiqing Dong; Xiaoqing Yi; Jing Guo; Jing Cai; Zehua Wang (Tumor Biology)
Metastatic or recurrent cervical cancer has limited treatment options and a high rate of mortality. Although anti-vascular endothelial growth factor drugs have shown great promise as a therapeutic target for treatment of advanced cervical cancer, drug resistance and class-specific side effects negate long-term benefits. The identification of alternative anti-angiogenic factors will be critical for future drug development for advanced or recurrent cervical cancer. In this study, we found that angiopoietins and Tie receptors were highly expressed in cervical cancer cells. Tie-2 expression in tumor cells predicted poorer prognosis. Wound closure assay and Transwell assay showed that upregulated or downregulated Ang-1 and Ang-2 expression promoted or reduced cervical cancer cell lines migration and invasion, respectively. In subcutaneous xenograft models of cervical cancer, downregulation of Ang-1 and Ang-2 attenuated tumor growth. The expression of vimentin and endomucin and microvessel density were all significantly decreased in the siAng-1 group and siAng-2 group relative to the infection control group. Our data support that dual inhibition of Ang-1 and Ang-2 may be an alternative target for anti-angiogenic adjuvant therapy in advanced or recurrent cervical squamous cell cancer.